The Science of Physics and the Philosophy: its possible reduction to the Philosophy of Aristotle and Thomas Aquinas (Research, Society and Development, 2022)
My thesis in this work is that unless Modern Physics (or, in general, Science), which is imbued with the Cartesian method, changes its scientific method so that it (theoretical and experimental), (or another Science that will "arise"), can explain the Essence of Man-Nature, according to the Philosophies of Aristotle and Thomas Aquinas.